2021
DOI: 10.3389/fcell.2021.701328
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Parameters Can Predict the Response to Erythropoiesis-Stimulating Agents in Myelodysplastic Syndrome Patients

Abstract: Oxidative stress has been implicated in the development of several types of cancer, including myelodysplastic syndromes (MDS), as well as in the resistance to treatment. In this work, we assessed the potential of oxidative stress parameters to predict the response to erythropoiesis-stimulating agents (ESAs) in lower-risk MDS patients. To this end, we analyzed the systemic levels of reactive species (peroxides and NO), antioxidant defenses (uric acid, vitamin E, vitamin A, GSH, GSSG, TAS, as well as GPX and GR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Then, 500 µl cell lysate with 1 mg/ml protein were added to 1.5 mM of 10 mM SDS, 2 ml of ethanol and 2 ml of n‐hexane, and lipids were extracted from the upper phase formed after centrifugation. Vitamin E (vit E) levels were quantified by reverse‐phase HPLC using an analytic column Spherisorb S10w (250 mm × 4.6 mm), eluted at 1.5 ml/min with n‐hexane modified with 0.9% methanol, and detected in a spectrophotometer (Gilson) at 287 nm 61 . The sample volume (20 µl) injected corresponded to 2 µg protein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, 500 µl cell lysate with 1 mg/ml protein were added to 1.5 mM of 10 mM SDS, 2 ml of ethanol and 2 ml of n‐hexane, and lipids were extracted from the upper phase formed after centrifugation. Vitamin E (vit E) levels were quantified by reverse‐phase HPLC using an analytic column Spherisorb S10w (250 mm × 4.6 mm), eluted at 1.5 ml/min with n‐hexane modified with 0.9% methanol, and detected in a spectrophotometer (Gilson) at 287 nm 61 . The sample volume (20 µl) injected corresponded to 2 µg protein.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin E (vit E) levels were quantified by reverse-phase HPLC using an analytic column Spherisorb S10w (250 mm × 4.6 mm), eluted at 1.5 ml/min with n-hexane modified with 0.9% methanol, and detected in a spectrophotometer (Gilson) at 287 nm. 61 The sample volume (20 µl) injected corresponded to 2 µg protein. A calibration curve made with known concentrations of αtocopherol was used to calculate the concentration of vitamin E present in the extracts, and results were expressed as µM.…”
Section: Measurement Of Vitamin E Levelsmentioning
confidence: 99%
“…Then, 500 µL cell lysate with 1 mg/mL protein were added to 1.5 mM of 10 mM SDS, 2 mL of ethanol and 2 mL of n-hexane, and lipids were extracted from the upper phase formed after centrifugation. Vitamin E (vit E) levels were quantified by reverse-phase HPLC using an analytic column Spherisorb S10w (250 mm × 4.6 mm), eluted at 1.5 mL/min with n-hexane modified with 0.9% methanol, and detected in a spectrophotometer (Gilson, Lewis Center, Ohio, USA) at 287 nm [59]. The sample volume injected (20 µL) corresponded to 2 µg protein.…”
Section: Measurement Of Vitamin E Levelsmentioning
confidence: 99%
“…As such, oxidative stress parameters, such as malondialdehyde, were suggested to be predictive biomarkers for treatment response in lower-risk MDS patients. 55 Hoeks et al 56 followed the progress of 256 lower-risk MDS patients over 3 years and found a progressive increase of malondialdehyde levels in the patients over time. Oxidative stress due to iron toxicity, especially among transfusion-dependent patients, damaged organs and led to inferior outcomes.…”
Section: Therapeutic Properties Of 6-shogaolmentioning
confidence: 99%